mSphere of Influence: Evolutionary Strategies To Sensitize Drug-Resistant Pathogens - Rebecca S. Shapiro (American Society for Microbiology, 2019)
ABSTRACT Rebecca S. Shapiro studies antimicrobial resistance and genetic interaction networks. In this mSphere of Influence article, she reflects on how the papers “Bacterial evolution of antibiotic hypersensitivity” by Lázár et al. (V. Lázár, G. Pal Singh, R. Spohn, I. Nagy, et al., Mol Syst Biol 9:700, 2013, https://doi.org/10.1038/msb.2013.57) and “Use of collateral sensitivity networks to design drug cycling protocols that avoid resistance development” by L. Imamovic and M. O. A. Sommer (Sci Transl Med 5:204ra132, 2013, https://doi.org/10.1126/scitranslmed.3006609) impacted her thinking about multigene interaction effects on drug resistance.